2009
DOI: 10.1073/pnas.0907109106
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of phosphoinositide-phospholipase C beta1 methylation predicts the responsiveness to azacitidine in high-risk MDS

Abstract: Lipid signaling pathways are involved in cell growth, differentiation, and apoptosis, and could have a role in the progression of myelodysplastic syndromes (MDS) into acute myeloid leukemia (AML). Indeed, recent studies showed that phosphoinositide-phospholipase (PI-PL)Cbeta1 mono-allelic deletion correlates with a higher risk of AML evolution. Also, a single patient treated with azacitidine, a DNA methyltransferase inhibitor currently used in MDS, displayed a direct correlation between PI-PLCbeta1 gene expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
99
1
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 100 publications
(109 citation statements)
references
References 34 publications
6
99
1
3
Order By: Relevance
“…Indeed, azacitidine favors the re-expression of FAS in neoplastic mast cells or PI-PLCbeta1 genes in MDS or sAML. 7,12 Here we show that the in vivo use of the drug also favors the re-appearance of Fas receptor in sAML-derived CD45 lo /CD34 þ cells, together with FAS promoter demethylation (Supplementary Figure S1).…”
Section: Letters To the Editormentioning
confidence: 73%
“…Indeed, azacitidine favors the re-expression of FAS in neoplastic mast cells or PI-PLCbeta1 genes in MDS or sAML. 7,12 Here we show that the in vivo use of the drug also favors the re-appearance of Fas receptor in sAML-derived CD45 lo /CD34 þ cells, together with FAS promoter demethylation (Supplementary Figure S1).…”
Section: Letters To the Editormentioning
confidence: 73%
“…24,25 PI-PLCb1 has also been demonstrated to have a role both in the genetic 26 and in the epigenetic mechanisms of MDS progression to AML. 27,28 As for this latter, recent studies showed not only that PI-PLCb1 promoter gene is hypermethylated in high-risk MDS patients but also that it can be a specific target for AZA. Indeed, the amount of PI-PLCb1 messenger RNA could predict the clinical response to AZA, therefore indicating a promising new tool in the evaluation of response to demethylating therapies.…”
Section: Introductionmentioning
confidence: 99%
“…The degree of PI-PLCb1 promoter methylation was quantified by a standard SYBR-Green Real-Time methylation-specific PCR method using the glyceraldehyde-3-phosphate-dehydrogenase as a reference gene, as previously described. 28 …”
Section: Nucleic Acids Extractionmentioning
confidence: 99%
See 2 more Smart Citations